2013
DOI: 10.1007/s13244-013-0259-3
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of solid urethral and peri-urethral lesions

Abstract: Solid urethral and peri-urethral lesions are rare and encompass benign and malignant aetiologies. A diagnosis without imaging is often challenging secondary to non-specific clinical symptoms and overlapping findings at the time of physical examination. Magnetic resonance (MR) imaging may be helpful in confirming a diagnosis while providing anatomical detail and delineating disease extent. This article reviews the normal MR anatomy of the male and female urethra, the MR appearance of solid primary and secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Elastin-rich submucosa appears comparatively hyperintense (arrowhead), and the innermost mucosa (dotted arrow) appears hypointense. b Coronal, and c sagittal T2-weighted images showing similar appearance of urethra; mucosa is not well appreciated (b bladder, v vagina) Table 1 Summary of an ideal magnetic resonance imaging of the female urethra protocol [16,19,20,40] Technique…”
Section: Urethral Diverticulummentioning
confidence: 99%
See 1 more Smart Citation
“…Elastin-rich submucosa appears comparatively hyperintense (arrowhead), and the innermost mucosa (dotted arrow) appears hypointense. b Coronal, and c sagittal T2-weighted images showing similar appearance of urethra; mucosa is not well appreciated (b bladder, v vagina) Table 1 Summary of an ideal magnetic resonance imaging of the female urethra protocol [16,19,20,40] Technique…”
Section: Urethral Diverticulummentioning
confidence: 99%
“…These include a range of benign and malignant lesions. Leiomyomas are an example of benign, solid, periurethral lesions that arise from the urethra, bladder neck, or vagina [20]. These usually demonstrate homogeneous low signal intensity on T1W images and variable signal intensity on T2W images (Fig.…”
Section: Solid Periurethral Lesionsmentioning
confidence: 99%
“…Although some reports are available in the literature, most of them elaborate either on pathological [2,3] or radiological [7,8] aspects. Therefore, treatment of such patients remains a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The distinction between urethral, peri-urethral, and anterior vaginal wall lesions may be difficult because of their anatomic proximity and overlapping clinical features. Imaging techniques such as computed tomography/magnetic resonance (CT/MR) (preferably MR) are helpful in diagnosis [7,8]. Cysto-urethrogram helps in excluding the urethral origin and invasion.…”
Section: Purposementioning
confidence: 99%
“…Lastly, there was a review conducted recently that addressed the utility of MRI in the setting of urethral and periurethral solid soft-tissue lesions [19]. Despite no recent studies on the topic, the historical literature suggested that MRI is most useful for male urethral tumors/solid lesions that are stage II or higher (due to lack of periurethral invasion in stage I disease, which limits MRI detection ability).…”
Section: Magnetic Resonance Urethrographymentioning
confidence: 99%